Predictors of Uncontrolled Hypertension Among Libyan Patients: A Cross-Sectional Study at Tripoli University Hospital - Rida Ben Fadel; Sana Taher Ashur (AlQalam Journal of Medical and Applied Sciences, 2025)
Poorly controlled blood pressure is associated with adverse health outcomes and increased mortality. This study aimed to describe the socio-demographic, clinical, and self-care profiles of hypertensive patients attending Tripoli University Hospital, with a focus on their blood pressure control status. It also examined the contribution of selected patient characteristics and self-care factors to uncontrolled blood pressure. A cross-sectional study was conducted among 335 patients, using an interviewer-based questionnaire, review of medical records, anthropometric measurement, and blood pressure measurement. Data were analyzed using SPSS software. A high prevalence of uncontrolled blood pressure was observed (64.5%). Non-adherence to antihypertensive medications (p<0.001, OR=6.201, 95% CI: 2.680-14.348), following a traditional diet (p=0.027, OR=2.205, 95% CI: 1.093-4.447), and not receiving lipid-lowering therapy (P=0.009, OR=2.530, 95% CI: 1.266-5.056) were significant predictors of uncontrolled blood pressure. Uncontrolled hypertension remains prevalent among patients in Tripoli. The findings support the role of medication adherence and dietary modification in blood pressure control. Interventions that enhance patients’ adherence to their prescribed treatment and adoption of antihypertensive dietary recommendations may reduce the burden of uncontrolled hypertension in Libya.